A New Species of the Genus Diplous, Subgenus Platidius (Coleoptera, Carabidae) from East Siberia - Zamotajlov, A.S. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Diplous dolini Zamotajlov, sp. n., a sibling species of D. depressus (Gebler), is described from East Siberia. It is distinguishable mainly by the structure of endophallus and size and shape of ventrite IX. The pathways of diversification of the subgenus Platidius in Siberia are briefly discussed. Описан Diplous dolini Zamotajlov, sp. n. из Восточной Сибири, вид-двойник D. de-pressus (Gebler). Он отличается, прежде всего, по структуре внутреннего мешка пениса, а также размером и формой IX вентрита. Кратко обсуждаются закономерности диверсификации подрода Platidius в Сибири.